Synchronization control techniques for shunt active power filter: an overview - Ranga Rao, Chegudi; Balamurugan, Ramadoss; Alla, RamaKoteswaraRao (Institute of Advanced Engineering and Science, 2023)
The phase synchronization control technique of shunt active power filter (SAPF) is discussed in this article. Due to the harmful effects of harmonic currents on power systems, the issue of decreasing their effects has generated a lot of research. A SAPF is acknowledged as the most dependable instrument in this area. The SAPF will detects the current harmonics present in the power system and also generates and injects the corrective current mitigation in the power system to reduce the current harmonics. This implies that, aside from the capacity to create compensating current, it is more essential to ensure that the SAPF can work in phase with the operational power system so that the compensating current will properly injected. As a result, while constructing SAPF control algorithms, correct synchronisation techniques must be incorporated. In this article, the different types of phase synchronization approach have been discussed such as phase-locked loop (PLL), adaptive linear neuron (Adaline), and unit vector. The results of the study may be used as a guideline and source of information for determining the best method for synchronising SAPF with the associated power system.